Analisis Proses Perekrutan PPPK Daerah di Kantor Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Gunungsitoli - Ribka Ratna Sari Zendrato; Meiman Hidayat Waruwu; Syah Abadi Mendrofa; Perlindungan Faebuadodo Hulu (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
The aim of this research is to find out how the Regional PPPK recruitment process is at the BKPSDM Gunungsitoli City Office and what are the obstacles in recruiting Regional PPPK at the Gunungsitoli City BKPSDM Office. This research uses qualitative research with observation and interview data collection methods. From the results of research from informants, the PPPK recruitment process for Gunungsitoli City involves several main stages which include planning, needs analysis, transparency, equality, registration process, acceptance process, and use of technology. In this research, several obstacles were also found, namely, technical obstacles, difficulties for prospective employees, and the reach of information. So researchers provide suggestions from the research results to evaluate and improve technological infrastructure, especially in the SSCASN registration system network application and provide adequate technical support for prospective employees who experience technical difficulties during the registration process. Carry out a more intensive outreach campaign regarding the PPPK recruitment process, especially to prospective employees.